The Development of Transformation Elements between the Fracture Mechanics Dependences and the Equations of the Reinforced Concrete Theory - Iakovenko, Igor; ., . (International Journal of Engineering and Technology, 2018)
It has been developed a transformational element that relates the dependencies of the fracture mechanics to the calculation of reinforced concrete structures by the second group of limiting states. It is described the features of cutting a two-cantilever element including a crack for constructing an effective instrument of calculation for reinforced concrete with allowance for physical nonlinearity, cracking processes, bond of reinforcement with concrete and the effect of discontinuity. The results of development of two-cantilever elements of fracture mechanics for various force effects are presented: bending, eccentric compression, central extension, and also in the zone of inclined cracks. It is obtained a new solution to the problem of the stressed-strained state of the reinforced concrete element in the zone immediately adjacent to the crack.Â